Pelatihan Pembelajaran Berbasis Video Collaborative Online Pada Pendidik TK As-Salam Kota Malang - Heru Herwanto; Dila Soraya; Setiadi Putro; Teguh Aprianto (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2021)
The COVID-19 pandemic that has been experienced throughout the world has resulted in the decline of several aspects, ranging from health, the economy, and the education system. Education which normally takes place offline (offline) is now hampered and must be replaced with online (online). Offline learning is different from online learning. A significant differentiator is the media in the learning process. Not all teachers can use technology optimally for the online learning process, especially for Kindergarten (TK) teachers. The solution to this problem is to conduct online collaborative video-based learning training for kindergarten teachers. The training will focus on how to use video conferencing applications (Google Meet and Zoom). This community service activity aims to provide training for kindergarten teachers who are expected to increase knowledge, especially in the field of technology for As Salam Kindergarten teachers and can improve interesting online learning models so that the material presented by the teacher can be well received by students. Pandemi COVID-19 yang dialami seluruh dunia mengakibatkan terpuruknya beberapa aspek, mulai dari kesehatan, perekonomian, dan juga sistem pendidikan. Pendidikan yang biasanya berjalan secara luar jaringan (luring) kini terhambat dan harus digantikan dengan dalam jaringan (daring). Cara pembelajaran luring berbeda dengan pembelajaran daring. Pembeda yang signifikan adalah media dalam proses pembelajaran. Tidak semua guru bisa menggunakan secara maksimal teknologi untuk proses pembelajaran daring terutama pada guru Taman Kanak-kanak(TK). Solusi dari permasalahan tersebut adalah dengan melakukan pelatihan pembelajaran berbasis video collaborative online kepada guru TK. Pelatihan akan berfokus pada cara penggunaan aplikasi video conference (Google Meet dan Zoom). Kegiatan pengabdian masyarakat ini bertujuan untuk memberikan pelatihan terhadap guru TK yang diharapkan dapat menambah pengetahuan khususnya bidang teknologi pada guru TK As Salam dan dapat meningkatkan model pembelajaran yang menarik secara daring sehingga materi yang disampaikan guru dapat diterima baik oleh murid.